Formation of competitive advantages of an industrial enterprise - Pererva, O. P.; Tkachova, N. P.; Romanchyk, T. V. (Miskolci Egyetem (Hungary), 2024)
The article examines the main approaches to the formation of competitive advantages of an industrial enterprise, and also analyzes the factors influencing competitiveness at different stages of its activity. A conceptual scheme-algorithm for the formation of market advantages of an industrial enterprise and its products in the B2B market has been developed and substantiated. Key factors of market success of products have been identified. Innovations and technological development are key drivers of competitive advantage. Key areas and spheres of competitive advantages of an industrial enterprise have been formed.
Формування конкурентних переваг промислового підприємства
Keywords: competitive advantages; B2B market; algorithm; model; products; market; factors